2022
DOI: 10.3389/fcell.2021.805195
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic, Metabolic, and Immune Crosstalk in Germinal-Center-Derived B-Cell Lymphomas: Unveiling New Vulnerabilities for Rational Combination Therapies

Abstract: B-cell non-Hodgkin lymphomas (B-NHLs) are highly heterogenous by genetic, phenotypic, and clinical appearance. Next-generation sequencing technologies and multi-dimensional data analyses have further refined the way these diseases can be more precisely classified by specific genomic, epigenomic, and transcriptomic characteristics. The molecular and genetic heterogeneity of B-NHLs may contribute to the poor outcome of some of these diseases, suggesting that more personalized precision-medicine approaches are ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 274 publications
(355 reference statements)
0
10
0
1
Order By: Relevance
“…In summary, glutamine, acetyl-CoA acetyltransferase 1 (ATAC1), indoleamine 2,3-dioxygenase (IDO), lactate, and Toll-like receptors (TLRs) are likely to be considered as novel "metabolic checkpoints", targeting of which could assist immune cells to achieve better anti-tumor effect. Noteworthily, epigenetic, metabolism, and immune crosslink in germinal-cancer-derived B-cell lymphomas (GCB) uncover a rational triple combination therapy (Serganova et al, 2021). GCB lymphoma is significantly heterogenous based on genetic, epigenetic, and clinical characteristics.…”
Section: Rational For Novel Immunotherapybased Combinationsmentioning
confidence: 99%
“…In summary, glutamine, acetyl-CoA acetyltransferase 1 (ATAC1), indoleamine 2,3-dioxygenase (IDO), lactate, and Toll-like receptors (TLRs) are likely to be considered as novel "metabolic checkpoints", targeting of which could assist immune cells to achieve better anti-tumor effect. Noteworthily, epigenetic, metabolism, and immune crosslink in germinal-cancer-derived B-cell lymphomas (GCB) uncover a rational triple combination therapy (Serganova et al, 2021). GCB lymphoma is significantly heterogenous based on genetic, epigenetic, and clinical characteristics.…”
Section: Rational For Novel Immunotherapybased Combinationsmentioning
confidence: 99%
“…While they all show efficacy and have been approved for low-grade lymphomas, their efficacy in DLBCL has generally been disappointing. They also show comparable toxicities to idelalisib, with copanlisib also having other serious side effects such as hyperglycemia and hypertension (reviewed in [ 88 ]).…”
Section: Anti-metabolic Therapies For Lymphomamentioning
confidence: 99%
“…A study of 120 DLBCL samples and 10 BL samples found that they all expressed MCT1 protein, but generally lacked expression of MCT4 [ 91 ]. A phase I expansion study of the MCT1 inhibitor AZD3965 in patients with relapsed/refractory DLBCL and BL has recently been reported [ 88 , 92 ]. Unfortunately, while the results of AZD3965 as a monotherapy were somewhat disappointing with only one out of eleven patients achieving a CR, this patient’s tumor did exhibit reduced FDG uptake as early as day 3 of therapy, consistent with the predicted impact of AZD3965 on glycolytic flux [ 92 ].…”
Section: Anti-metabolic Therapies For Lymphomamentioning
confidence: 99%
“…Moreover, CREBBP and EP300 respectively encode CBP and p300 proteins, both of which possess histone acetyltransferase activity. Abnormal acetylation caused by CREBBP and EP300 variations inactivates p53 and the transcriptional repressor BCL6, favoring the lymphomagenesis 72–74 . Additionally, EZH2 is involved in the regulation of pathophysiological processes such as cell cycle, senescence, cell differentiation, and tumorigenesis by catalyzing the trimethylation of lysine at the 27th position of histone H3 (H3K27m3) and thereby inhibiting the expression of target genes 75 …”
Section: Molecular Features Of Primary Extranodal Dlbclsmentioning
confidence: 99%